Effect of Azospirillum sp. and Corncob Biochar on Glycine max L. Growth in Saline Soil - Ni'mah, Farihatun; Yuliani, Yuliani (LenteraBio : Berkala Ilmiah Biologi, 2022)
Soybean (Glycine max L.) is the most popular bean in Indonesia. The high demand for soybeans is due the land narrowness for agriculture and suboptimal use of marginal land in Indonesia. Processing saline land into agriculture land can be developed to increase national soybean production. This study aims to find out the effect of Azospirillum sp., corncob biochar, and their interaction on soybean growth in saline soil. The research use two-factor of Randomized Block Design (RBD) method, and three repetition. The first factor is the concentration of Azospirillum sp., A0=0 mL, A1=20 mL, and A2=40 mL. The second factor is te dose of corncob biochar, T0=0 gram, T1=115 gram, T2=230 gram, and T3=315 gram. Growth parameters were observing plant height, number of leaves, root length, leaf area, and wet weight at 35 DAP. Data analysis was performed using two-way ANOVA followed by Duncan’s test. The results showed that Azospirilum sp. and corncob biochar had a significant effect on all growth parameters. There was no interaction between Azospiillum sp. and corncob biochar on the growth of soybean. (A2T3) 40 mL treatment on Azospirillum sp. and 315 gram of biochar has showed the best results on all parameters soybean growth.